Attachment Change in the Beginning Stages of Therapy: Examining Change Trajectories for Avoidance and Anxiety. (28th December 2015) - Seedall, Ryan B.; Butler, Mark H.; Zamora, Justin P.; Yang, Chongming
Abstract : The purpose of this study was to investigate the nature of self‐reported attachment change (avoidance and anxiety) in the context of six sessions of couple therapy designed to emphasize both therapist‐centered and couple‐centered (i.e., enactment‐based) clinical process during the beginning stages of therapy. A total of 48 couples with at least one partner who reported clinically significant relationship dissatisfaction participated in this study. Findings confirmed that some couples experience positive attachment‐related change (anxiety or avoidance), while also identifying a subset of individuals who may not experience optimal levels of attachment‐related change. In addition, findings point toward both differences and similarities between change trajectories for avoidance and anxiety. Finally, there was evidence that socio‐demographic factors may be associated with attachment change.